Islam’s Market Ideology: A Brief Outline - Abdul-Rahim Mohammed Adada (Islamic Economics Journal, 2019)
Many of the studies on the Islamic market doctrine have failed to integrate the idea within the broad social objective of its Islamic doctrinal origin. Consequently, the outcomes of such studies have only partially explicated the Islamic market theory. This brief study attempts to contextualize the Islamic market ideology within the broad social goal of the Islamic Shari’ah (law), in order to give it a more complete understanding. Using an interpretative approach that attempts to integrate market moral injunctions, pricing and profit, and price control, among others into the broader social doctrine of Islam, we established that the Islamic market ideology, broadly, seeks to promote the overall economic well-being of the members of society through creating fair opportunities for economic gains, enforcing the right to private property, and curbing exploitative tendencies of economic agents towards one another, among other things. Consequently, the Islamic market ideology is founded on the ideals of economic justice, which, generally, emphasize fairness as a moral duty enforceable by the state. It is further established that the individual has the right to engage in exchange activities and earn fair rewards, and this must not, ordinarily, be interfered with. However, when, in the course of exercising this right, the individual’s pursuit of self-interest puts the overall public welfare into jeopardy, the state is obliged to give public welfare precedence over individual self-interests. Thus, there is room for the state to intervene even in pricing; though, under normal circumstances, prices in the market should depend on the prevailing market conditions.